Facile fabrication and SERS performance of polymer/Ag core-shell microspheres via the reverse breath figure accompanied by in situ reduction. (22nd June 2022) - Li, Yongjiang; Ma, Xiaoyan; Ma, Jingyu; Zhang, Zongwu; Niu, Zhaoqi; Chen, Fang
Abstract: A new facile fabrication process of the polymer/Ag core-shell microspheres is demonstrated via the reverse breath figure method accompanied by in situ reduction. In contrast to traditional approaches, which require the prior preparation of polymer microspheres, the star-shaped polyhedral oligomeric silsesquioxane (POSS) amphiphilic block copolymers solution containing AgNO3 is cast under ethanol vapor for the formation of polymer/AgNO3 core-shell microspheres in one step. The influence of polymer molecular structures, solvent, non-solvent and metal salt on the morphology of polymer microspheres was analyzed. Then the AgNO3 can be reduced in situ to form Ag nanoparticles on the surface of polymer microspheres, which resulted in the formation of polymer/Ag core-shell microspheres. The reduced Ag nanoparticles were homogeneously deposited on the surfaces of polymer microspheres, which can exhibit good performance in the surface-enhanced Raman scattering (SERS). The polymer/Ag core-shell microspheres substrate showed a high detection sensitivity (enhancement factor 2.49 × 10 6 ) with excellent uniformity and reproducibility for Rhodamine 6G (R6G) (relative standard deviation of the intensity at 612 cm −1 was 6.19%＜20%). The proposed strategy is facile to implement and thus a promising new method for the preparation of polymer/metal core-shell microspheres. Graphical abstract: Image 1 Highlights: First report of fabrication of polymer/Ag core-shell microspheres via reverse breath figure accompanied by in situ reduction. Do not require the prior preparation of polymer microspheres. The influence on the morphology of polymer/Ag microspheres was analyzed.